ACCURACY OF INDEX FLOOD METHOD APPLIED IN TWO DIFFERENT REGIONS IN INDONESIA - R. T. Lopa (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
Problems of having relatively accurate estimates of design discharge values in ungauged catchments remains. There is an empirical equation in the area which gives appropriate estimates, but it needs some efforts in measuring catchment parameters, which is time consuming in line with the catchment area. A relatively simple method in doing so is the known Index Flood Method. The accuracy of this method in its application in Indonesia has never been examined. An understanding of its accuracy will provide the design with more confidence. Keywords: Index flood method, direct flood method.